2015
DOI: 10.1111/bcp.12623
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a vasomotor cyclo‐oxygenase dependent mechanism of sensitization at the cutaneous level

Abstract: AIMSCurrent-induced vasodilation (CIV) is an axon-reflex response observed during monopolar current application such as iontophoresis. Cyclo-oxygenase derivates (COD) participate in CIV and act as sensitizing agents at the anodal level. Mechanisms involved during cathodal current application (CCA) are partially unknown. In a randomized double-blind crossover trial, we tested in 16 healthy subjects (i) the influence of the inter-stimulation interval (I-I) by comparing CIV following all-at-once 10 s CCA against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Indeed both capsazepine and amiloride could block impulse conduction in sensory nerves (Hayes et al, 2007), thereby attenuating CGRP and substance P release (Franco-Cereceda et al, 1993;Santicioli et al, 1993;Zhong and Wang, 2007). Moreover capsazepine, CGRP8-37 and the NK1 antagonist L703,606 could reduce prostacyclin production (Gallicchio et al, 2006;Harada et al, 2003;Mizutani et al, 2009) and we demonstrated that prostacyclin plays a major role in cathodal CIV in rats (Gohin et al, 2011), as recently confirmed in humans (Mahe et al, 2015). Although each drug is selective for a channel or receptor, it may not be specific in its action, given a plausible explanation for the large decrease in cathodal CIV observed for each individual blockade.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed both capsazepine and amiloride could block impulse conduction in sensory nerves (Hayes et al, 2007), thereby attenuating CGRP and substance P release (Franco-Cereceda et al, 1993;Santicioli et al, 1993;Zhong and Wang, 2007). Moreover capsazepine, CGRP8-37 and the NK1 antagonist L703,606 could reduce prostacyclin production (Gallicchio et al, 2006;Harada et al, 2003;Mizutani et al, 2009) and we demonstrated that prostacyclin plays a major role in cathodal CIV in rats (Gohin et al, 2011), as recently confirmed in humans (Mahe et al, 2015). Although each drug is selective for a channel or receptor, it may not be specific in its action, given a plausible explanation for the large decrease in cathodal CIV observed for each individual blockade.…”
Section: Discussionsupporting
confidence: 78%
“…We hypothesize that this overexpression could be linked to hypofunction of TRPV-1 that would induce a diminished microvascular peak response in our T1D patients, but this remains to be studied. In our study we also used the cathodal CIV, a second axon reflex test that is partially mediated by prostaglandins 28 . This test is based on the anodal CIV test that has been widely used and studied in the literature 29 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The current application was delivered on the active probe in two consecutive 5-second applications separated by 4 minutes28. For CIV, we studied the late-plateau response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation